2002
DOI: 10.1128/jcm.40.7.2498-2503.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Clinical and Environmental Strains of Salmonella enterica Serotype Weltevreden Isolated in Malaysia

Abstract: The incidence of food-borne salmonellosis due to Salmonella enterica serotype Weltevreden is reported to be on the increase in Malaysia. The pulsed-field gel electrophoresis (PFGE) subtyping method was used to assess the extent of genetic diversity and clonality of Salmonella serotype Weltevreden strains from humans and the environment. PFGE of XbaI-digested chromosomal DNA from 95 strains of Salmonella serotype Weltevreden gave 39 distinct profiles with a wide range of Dice coefficients (0.27 to 1.00), indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 16 publications
6
75
2
Order By: Relevance
“…There are over 1.3 billion foodborne diarrhea cases occurred worldwide annually, resulting in 3 million deaths (Mastropeni and Maskell 2006). In Malaysia, the incidence rate of foodborne disease is about 8,640 cases reported by the Ministry of Health for the year 1999, where 811 (9.4%) cases were due to Salmonella infections (Thong et al 2002). Most Salmonella enterica serovars can cause illnesses in humans.…”
Section: Introductionmentioning
confidence: 99%
“…There are over 1.3 billion foodborne diarrhea cases occurred worldwide annually, resulting in 3 million deaths (Mastropeni and Maskell 2006). In Malaysia, the incidence rate of foodborne disease is about 8,640 cases reported by the Ministry of Health for the year 1999, where 811 (9.4%) cases were due to Salmonella infections (Thong et al 2002). Most Salmonella enterica serovars can cause illnesses in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Processing isolates using different restriction enzymes can yield distinct PFGE patterns and, subsequently, discordant interpretations of strain relationships (16). Genetic diversity in closely related outbreak strains (1,16) or clonally dominant endemic strains (17) may be insufficient to permit their correct interpretation, and some isolates with different phenotypes share the same PFGE pattern (18). PFGE results may correlate poorly with the true relatedness of isolates (16,19,20), especially among more distantly related strains (21), and at least one study reported that greater discriminatory power could be obtained through alternative molecular approaches (22).…”
mentioning
confidence: 99%
“…S. weltevreden was isolated from beef and was similar reported from Thailand (Bangtrakulnonth et al 2004) and has been the most prevalent bovine Salmonella serovars in Vietnam (Vo et al 2006). In Malaysia, food poisoning cases reported by the Ministry of Health for the year 1999, of 8,640 cases, 811 (9.4%) were due to Salmonella (Thong et al 2002). In addition, report of food poisoning from Division of Food Safety and Quality, Department of Health Kelantan showed the result in 2009, in 11 of 56 episodes (19.6%), Salmonella was isolated from food samples collected during the outbreak investigation.…”
Section: Resultsmentioning
confidence: 67%